Clinical Perspectives of ERCC1 in Bladder Cancer - Koutsoukos, Konstantinos (Int J Mol Sci, 2020)
ERCC1 is a key regulator of nucleotide excision repair (NER) pathway that repairs bulky DNA adducts, including intrastrand DNA adducts and interstrand crosslinks (ICLs). Overexpression of ERCC1 has been linked to increased DNA repair capacity and platinum resistance in solid tumors. Multiple single nucleotide polymorphisms (SNPs) have been detected in ERCC1 gene that may affect ERCC1 protein expression. Platinum-based treatment remains the cornerstone of urothelial cancer treatment. Given the expanding application of neoadjuvant and adjuvant chemotherapy in locally advanced bladder cancer, there is an emerging need for biomarkers that could distinguish potential responders to cisplatin treatment. Extensive research has been done regarding the prognostic and predictive role of ERCC1 gene expression and polymorphisms in bladder cancer. Moreover, novel compounds have been recently developed to target ERCC1 protein function in order to maximize sensitivity to cisplatin. We aim to review all the existing literature regarding the role of the ERCC1 gene in bladder cancer and address future perspectives for its clinical application.